Method for constructing pulmonary nodule computer-aided detection model - LIU XIAOJUN; TAO TAO; ZHANG WEI; YIN TONG (2020)
The present invention discloses a method for constructing a pulmonary nodule computer-aided detection model. The method comprises the following steps: obtaining bronchial epithelial cells of a subjectand extracting RNA; constructing a double-stranded cDNA library according to the RNA and conducting sequencing; comparing a sequencing result with a reference genome and selecting a differential significant gene and a differential significant variation of the subject; using a vector formed by combining the differential significant gene and the differential significant variation, and benign and malignant pulmonary nodules as sample data; randomly dividing the sample data of the subject into a training set and a prediction set and carrying out multiple times of training on the training set andthe prediction set on the basis of a support vector machine model adopting a radial basis kernel function to obtain a model output value of the prediction set; and carrying out non-dimensionalizationon clinical data and CT ima